Efektivitas Target Pembiayaan Baitul Maal Wa Tamwil Surya Gemilang Desa Sedayulawas Kecamatan Brondong Kabupaten Lamongan - Abdul Muiz Hamid; Sri Herianingrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This study aims to determine the effectiveness of targeted financing in BMT Surya Gemilang village Sedayulawas Brondong distridt of Lamongan through the financing to its customers and financial report statements, as well as the customers’ trust in taking capital.This study used a qualitative approach and descriptive case study. To collect the data, this study uses purposive sampling and snowball technique. The results of this study show that the effectiveness of targeted financing is annually achieved as planned by BMT Surya Gemilang. This is reflected in the provision of financing to customers and the financial reports which always reach the target as well as the smooth repayment of loans by customers. REFERENCESAl-Qur'an dan Terjemahanya. 2005. Syamil Al Qur'an. Bandung: PT. Syaamil Cipta Media.Andriani. 2005. BAITUL MAAL WAT TAMWIL Konsep dan Mekanisme di Indonesia,(Online), Volume 14, No.2, http://idb2.wikispaces.com/file/vi ew/rd2012.pdf, diakses 14 April 2012).Antonio, Muhammad Syafi’i. 2001. Bank Syariah: Dari Teori ke Praktik. Jakarta: Gema Insani Press.---------. 2005. Manajemen Dana Bank Syariah, Edisi Pertama. Jakarta: Gema Insani Press.Dewan Syariah Nasional MUI. 2000. Fatwa DSN MUI No. 04/DSNMUI/IV/2000 Tentang Murabahah.-------- . 2000. Fatwa DSN MUI No. 05/DSNMUI/IV/2000 Tentang Jual Beli Salam.-------- . 2000. Fatwa DSN MUI No. 06/DSN-MUI/IV/2000 Tentang Jual Beli Istishna’.-------- . 2000. Fatwa DSN MUI No. 07/DSN-MUI/IV/2000 Tentang Pembiayaan Mudharanah (Qiradh).-------- . 2000. Fatwa DSN MUI No. 08/DSN-MUI/IV/2000 Tentang Pembiayaan Musyarakah.-------- . 2000. Fatwa DSN MUI No. 09/DSN-MUI/IV/2000 Tentang Pembiayaan Ijarah.-------- . 2001. Fatwa DSN MUI No. 19/DSNMUI/IV/2001 Tentang Al-Qardh.-------- . 2002. Fatwa DSN MUI No. 27/DSNMUI/III/2002 Tentang Al-Ijarah AlMuntahiyah Bi Al-Tamlik.Huda, Nurul dan M. Heykal. 2010. Lembaga Keuangan Islam: Tinjauan Teoretis dan Praktis. Jakarta: Prenada Media Group.Ibnu Rusyd, Muhammad Ibnu Ahmad Ibnu Muhammad. 1988. Bidayatul Mujtihad wa Nihayatul Muqtashid. Beirut: Darul-Qalam.Ilmi, Makhalul. 2002. Teori dan Praktek Lembaga Mikro Keuangan Syariah. Yogyakarta: UII Press.Karim, Adiwarman. 2004, Bank Islam Analisis Fiqih dan Keuangan. Jakarta: PT. Raja Grafindo Persada.Lubis, Suhrawardi. 2004. Hukum Ekonomi Islam. Jakarta: Sinar Grafika.Muhammad. 2006. Bank Syariah Analisa Kekuatan, Kelamahan, Peluang dan Ancaman. Edisi Kedua. Yogyakarta: Ekonisia.Noviandi, Bares Aulia. 2009. Analisis FaktorFaktor Pengambilan Pembiayaan dan Penilaian Efektifitas Pembiayaan Syariah Bagi Usaha Kecil pada BMT Dana Insani Kabupaten Gunung Kidul Propinsi Yogyakarta. Skripsi tidak diterbitkan. Bogor. Fakultas Pertanian Institut Pertanian Bogor.Republik Indonesia. Peraturan Menteri Negara Koperasi dan Usaha Kecil dan Menengah Republik Indonesia No. 35.2/PER/M.KUKM/X/2007. 2007. (online), (http://www.depkop.go.id/regula si/cat_view/34-regulasi/205- peraturan-menteri-kjks-ujkskoperasi-2008.html diakses 2 Mei 2012)Ridwan, Muhammad. 2004. Manajemen Baitul Maal Wat Tamwil (BMT). Yogyakarta: UII Press.Sabiq, Sayyid. 1988. Fikih Sunnah 12. Bandung : PT Al-Ma’Arif.Sakai, Minako & Kacung Marijan. 2008. Mendayagunakan Pembiayaan Mikro Islami, (Online), (www.smeru.or.id/report/training/ menjembatani...dan.../73.pdf, diakses 14 Juli 2012)Sudarsono, Heri. 2008. Bank & Lembaga Keuangan Syariah Deskripsi dan Ilustrasi Edisi Ketiga. Yogyakarta: Ekonisia.Suhendi, Hendi. 2009. Strategi Optimalisasi Peran BMT Sebagai Penggerak Sektor Usaha.Syafar, Muhammad. 2006. Analisis Efektifitas Pembiayaan Sistem Syariah Terhadap Petani Agri Bisnis Sayuran pada Program UPK Ikhtiar Yayasan Perahu Bogor. Skripsi tidak diterbitkan. Bogor. Fakultas Ekonomi Manajemen Institut Pertanian Bogor.Yin, Robert K. 2006. Studi Kasus: Desain dan Metode, Terjemahan. Jakarta: PT Grafindo Persada.